EMOSI TOKOH DALAM NOVEL RUMAH UNTUK ALIE KARYA LENN LIU: KAJIAN PSIKOLOGI SASTRA - Musdalifah Suci; Yenny Puspita; Yessi Fitriani (Universitas Negeri Makassar, 2025)
The purpose of this study is to describe the emotions of the characters in the novel Rumah untuk Alie by Lenn Liu using David Krech's emotion classification theory. This research is a descriptive qualitative research. The research data source is the novel Rumah Untuk Alie by Lenn Liu. The steps of data analysis in the research, namely: reading the novel in its entirety and repeatedly; making a synopsis of the novel; searching and understanding the data; classifying the emotions of the characters; describing the results of the classification of emotions in the characters; and concluding the findings. The results showed that the characters' emotions found in the novel Rumah untuk Alie by Lenn Liu are the concepts of guilt, suppressed guilt, self-punishment, shame, sadness, hatred, and love. The most common emotion found is the emotion of hatred while the least found is the emotion of shame. These results are findings from quotes or dialogue on each character consisting of six characters, namely: Alie, Abhimanyu, Sadipta, Rendra, Samuel, and Natta.